Kasih Persaudaraan di dalam Kristus: Pembekalan Sekolah Minggu, Remaja, Naposobulung HKBP Siraituruk tentang Tri Tugas Panggilan Gereja - Turnip, Ricardo S.; Sianipar, Efran; Simanjuntak, Jonri (CV. Creative Tugu Pena, 2023)
In era’s chruch life, more effective and efficient services are needed in order to Improve the spirituality of the chruch and congregation. Through this, there are several tips for the duties of the chruch’s calling that are needed by the congregation, namely Marturia (bearing witness), Koinonia (allying), and Diakonia (Serving). Through community service activities in HKBP Siraituruk, we try to put into practice the teachings of the chruch’s calling that have been studied in lectures. This activity was supported by several students of STT HKBP Pematang Sinatar who were guided by the academic Supervisor Pdt. Dr. Ricardo Turnip. In this community service activity, there are several activities carried out in it, starting from a mutual cooperatiom event cleaning the church yard (Diakonia), bible study service accompanied by bible games (Marturia and Diakonia), service to Sunday school children, choir evangelization and friendly event at Sunday worship followed by a group photo session after Sunday worship. Keywords: Tri Tugas Panggilan Gereja, Marturia, Koinonia, Diakonia